Answer:
f(x) = (x - 1)(x + 2)(x - 3)
Step-by-step explanation:
We are given the following function and we are to factorize it completely:
[tex] f ( x ) = x ^ 3 - 2 x ^ 2 - 5 x + 6 [/tex]
To factorize this completely, we will use the rational roots theorem.
[tex] x ^ 3 - 2 x ^ 2 - 5 x + 6 [/tex]
P = ± multiples of constant term [tex]6 = \pm1, \pm2, \pm3, \pm6[/tex]
Q = ± multiples of the coefficient of highest degree term [tex] = \pm1[/tex]
So the factors will be [tex]\frac{P}{Q}[/tex].
The possible rational roots are [tex] 1, \pm2, \pm3, \pm6[/tex].
1 is a confirmed root and now we will use synthetic division to find the other rational roots:
1 | 1 -2 -5 6
1 -1 -6
___________
1 -1 -6 0
So the polynomial will be [tex](x^2 - x - 6)[/tex] which can we factorize now.
[tex]x^2 - x - 6 = x^2 - 3x + 2x - 6[/tex]
[tex]x(x - 3) + 2(x - 3) = (x+2)(x-3)[/tex]
Therefore, the completely factorized form of the given function is f(x) = (x - 1)(x + 2)(x - 3).